Effects of Post-Fire Rehydration on the Mechanical Properties of Slag-Modified Concrete - Guilherme Palla Teixeira; José Carlos Lopes Ribeiro; Leonardo Gonçalves Pedroti; Gustavo Henrique Nalon (Buildings)
Although previous research has examined the mechanical properties of concrete exposed to high temperatures, further investigation is needed into the effects of post-fire curing on the recovery of strength and stiffness of sustainable concretes produced with slag-modified cement. This study conducted an experimental analysis of the residual compressive strength and modulus of elasticity of different types of concrete (20 MPa or 30 MPa) exposed to varying maximum temperature levels (200 °C, 400 °C, 600 °C, 800 °C) and post-fire treatments (with or without rehydration). The concrete specimens were produced using Portland cement CP II-E-32. The rehydration method involved one day of water curing, followed by 14 days of air curing. Statistical analyses revealed potential improvements in the mechanical properties of concretes produced with slag-modified cement due to rehydration processes after exposure to different temperatures levels. The highest values of the relative residual strength factor (Φc) were observed in specimens exposed to a maximum temperature of 600 °C, ranging from 0.862 to 0.905. The highest values of the relative residual elastic modulus factor (ψc) were verified for a maximum temperature of 200 °C, ranging from 0.720 to 0.778. The experimental results were compared with strength and stiffness predictions of design codes. The inclusion of slag in concrete reduced microcracking during the rehydration process due to the reduced amount of calcium hydroxide in the cementitious matrix, increasing the concrete’s relative residual strength and stiffness after post-fire curing.